Analysis of Adjuvant Chemotherapy on Pathological Remission of Breast Cancer - Bing Jiang (Hindawi Limited, 2021)
With the continuous development of the concept of diagnosis and treatment, the current industry’s treatment model has developed into a multidisciplinary comprehensive treatment. That is, in view of the pathological characteristics and clinical stages of breast cancer, corresponding methods such as surgery, chemotherapy, endocrine therapy, radiotherapy, and biological targeted therapy are adopted to provide comprehensive treatment of patients with multiple disciplines. This paper combines experimental research to research and analyze the degree of pathological remission of breast cancer by adjuvant chemotherapy and combines investigation and analysis and group trials to study and explore the effect of adjuvant chemotherapy. Moreover, this paper fully considers the patient’s response to neoadjuvant chemotherapy and compares the changes in tumor cell abundance before and after chemotherapy to observe the response of the patient’s primary tumor to chemotherapy at a microscopic level. Therefore, this study has made a relatively objective and accurate evaluation of the chemotherapy efficacy of tumor tissues, which can provide a reference for subsequent related research.